Transgender rights and politics : groups, issue framing, and policy adoption - Taylor, Jami K.; Haider-Markel, Donald P. (University of Michigan Press, 2014)
To date, media and scholarly attention to gay politics and policy has focused on the morality debates over sexual orientation and the legal aspects of rights for non-heterosexuals. However, transgender concerns as such have received little attention. As transgender activism has become more visible, policymakers, both in the United States and around the world, have begun to respond to demands for more equitable treatment. Jami K. Taylor and Donald P. Haider-Markel bring together new research employing the concepts and tools of political science to explore the politics of transgender rights. Volume contributors address the framing of transgender rights in the U.S. and in Latin America. They discuss transgender interest groups, the inclusion of transgender activists in advocacy coalitions, policy diffusion at the state and local levels, and, importantly, the implementation of transgender public policy. This volume sets the standard for empirical research on transgender politics and demonstrates that the study of this topic can contribute to the understanding of larger questions in the field of political science. -- Provided by publisher.